HARMONISASI NILAI TUKAR MENUKAR PUPUK KANDANG DENGAN ALAT PERTERNAKAN DI NAGARI KOTO BARU SUNGAI TARAB DALAM PERPEKTIF FIQH MUAMALAH - Sri Wahyuni; Sri Yunarti (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2022)
The subject of the study is the Exchange Rate of Manure Exchange for Livestock Equipment in Nagari Koto Baru Sungai Tarab from the Fiqh Muamalah Perspective. The purpose of this study is to identify and analyze the motives for the exchange of manure and livestock equipment in Nagari Koto Baru Sungai Tarab, as well as to determine people's perceptions related to the status of manure, to determine the value of the benefits of exchanging manure with livestock equipment in Nagari Koto Baru Sungai Tarab in the perspective of fiqh muamalah. The research used was field research which was descriptive and qualitative in nature. Data collection techniques were observation, interviews, and documentation. Data validity assurance technique with source triangulation. This study found results, first in terms of the motive for the implementation of the exchange of manure with livestock equipment in Nagari Koto Baru Sungai Tarab triggered by the farmer's need for manure for agriculture to support crop yields, thus encouraging farmers to obtain manure from livestock by exchanging the manure. with livestock. This exchange activity does not have a clear contract and there is no agreement regarding the amount and object of goods exchanged. Second, from the public's perception of manure, manure is an important requirement that is beneficial for agricultural land. The community has never traded manure because it is considered unclean to be traded. Third, in terms of the value of the exchange benefits of exchanging manure for livestock equipment, this is in accordance with Allah's commands in surah Al-Maidah verse 2 and An-Nisa verse 29 and on the muamalah principle regarding muamalah transactions that must be based on willingness, helping each other, and not eating up wealth. each other in a bad way.